2016
DOI: 10.1101/gad.280685.116
|View full text |Cite
|
Sign up to set email alerts
|

Asf1 facilitates dephosphorylation of Rad53 after DNA double-strand break repair

Abstract: To allow for sufficient time to repair DNA double-stranded breaks (DSBs), eukaryotic cells activate the DNA damage checkpoint. In budding yeast, Rad53 (mammalian Chk2) phosphorylation parallels the persistence of the unrepaired DSB and is extinguished when repair is complete in a process termed recovery or when the cells adapt to the DNA damage checkpoint. A strain containing a slowly repaired DSB does not require the histone chaperone Asf1 to resume cell cycle progression after DSB repair. When a second, rapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 75 publications
1
26
0
Order By: Relevance
“…ASF1a promotes H3 acetylation at lys56 by the CBP/p300 acetyltransferase, which is required for nucleosome reassembly after DNA repair (Das et al, 2009; Groth et al, 2007). ASF1 is required for checkpoint recovery and the return to normal cell cycle after DNA damage repair (Tsabar et al, 2016), but there is no report that shows ASF1 is directly involved in DSB repair. We have discovered that ASF1a is specifically required to promote NHEJ and thus suppress HR.…”
mentioning
confidence: 99%
“…ASF1a promotes H3 acetylation at lys56 by the CBP/p300 acetyltransferase, which is required for nucleosome reassembly after DNA repair (Das et al, 2009; Groth et al, 2007). ASF1 is required for checkpoint recovery and the return to normal cell cycle after DNA damage repair (Tsabar et al, 2016), but there is no report that shows ASF1 is directly involved in DSB repair. We have discovered that ASF1a is specifically required to promote NHEJ and thus suppress HR.…”
mentioning
confidence: 99%
“…The Haber group recently reported that Asf1 and Rtt101 are required for checkpoint recovery, but in their hands they only had this role when they induced two DSBs [ 58 ], not one DSB as is the case in our studies [ 24 ] Fig 3 . This may be related to the fact that the Haber lab only observed defective checkpoint recovery in response to a single DSB when they remove both Asf1 and CAF-1 at the same time, but not with the individual mutations [ 35 ] as is the case in our hands [ 24 ].…”
Section: Discussionmentioning
confidence: 58%
“…Based on these findings and on our Ddc2-GFP localization data, we postulate that the degradation of the Ddc2 pool, which is not localized to chromatin could be used to limit continuous Mec1-Ddc2 recruitment to the break site in the presence of a persistent DNA lesion. Conditional depletion of Ddc2 by using an auxin-inducible degron system causes rapid Rad53 dephosphorylation (Tsabar et al, 2016). Additionally, the overexpression of Ddc2, but not Mec1, is shown to cause a hyperactivation of the checkpoint activity .…”
Section: Discussionmentioning
confidence: 96%